2013
DOI: 10.1113/jphysiol.2012.236604
|View full text |Cite
|
Sign up to set email alerts
|

Taste responses in mice lacking taste receptor subunit T1R1

Abstract: Key points• The taste receptor heterodimer T1R1 + T1R3, metabotropic glutamate receptors (mGluRs) and/or their variants may function as umami taste receptors.• Here, we used newly developed T1R1 −/− mice and examined the role of T1R1 and mGluRs in taste detection.• The T1R1−/− mice exhibited seriously diminished synergistic responses to glutamate and inosine monophosphate but not to glutamate alone and significantly smaller responses to sweeteners.• Addition of mGluR antagonists significantly inhibited respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 47 publications
2
95
0
Order By: Relevance
“…However, studies using an independently generated Tas1r3 -knockout line (see above) showed that the behavioural and neural responses of these mice to umami compounds (MSG and IMP) were nearly normal 22, 40 . Furthermore, a second line of mice in which Tas1r1 was knocked out also demonstrated near-normal responses to umami compounds in taste bud cells and nerves; the only major change was that the nucleotide-mediated augmentation of umami taste was lost 41 . Thus, it seems that T1R1–T1R3 responds primarily to mixtures of MSG and nucleotides.…”
Section: Chemosensory Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies using an independently generated Tas1r3 -knockout line (see above) showed that the behavioural and neural responses of these mice to umami compounds (MSG and IMP) were nearly normal 22, 40 . Furthermore, a second line of mice in which Tas1r1 was knocked out also demonstrated near-normal responses to umami compounds in taste bud cells and nerves; the only major change was that the nucleotide-mediated augmentation of umami taste was lost 41 . Thus, it seems that T1R1–T1R3 responds primarily to mixtures of MSG and nucleotides.…”
Section: Chemosensory Transductionmentioning
confidence: 99%
“…Most type II cells express one class of taste GPCR — namely, taste receptor type 1 (T1R) or T2R — and correspondingly respond only to one taste quality (for example, sweet or bitter, but not both) 131, 132 . It should be noted that T1R1, T1R2 and T1R3 are often co-expressed in taste bud cells, and, accordingly, responses to both sweet and umami stimuli can be detected in the same cells 41, 114 . The type II cells in a taste bud can differ in their expression of taste GPCRs such that each taste bud can respond to multiple taste stimuli.…”
Section: Figurementioning
confidence: 99%
“…In this study we used the paradigmatic umami ligand MSG to activate T1R1/T1R3 receptors. Since MSG may also activate other amino acid-sensing receptors, we also employed the 5=-ribonucleotide IMP, an allosteric activator specific for T1R1 (27,49). Thus the combination of MSG and IMP shows that the effects are specific to T1R1/T1R3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inosine 5=-monophosphate (IMP) is a potentiator of T1R1/T1R3 activation but is not a potentiator at other putative umami receptors (CaSR, metabotropic glutamate receptor, or G protein-coupled receptor family C, group 6, member A) (12,27,33,49). Therefore, IMP can be used to pharmacologically determine if T1R1/T1R3 receptors are involved in changes in GI motility, as has been done in the characterization of umami taste.…”
mentioning
confidence: 99%
“…18,26 Although some evidence exists to the contrary, 27 it has been generally accepted that individual type II receptor cells only express receptors for a specific taste quality -sweet, umami, or bitter (i.e., these three classes of taste stimuli are detected by nonoverlapping populations of taste cells within the taste bud). Sweet tastants, including artificial sweeteners, bind to a heterodimer of the G protein-coupled receptors, T1R2 and T1R3.…”
Section: Taste Bud Anatomy and Physiologymentioning
confidence: 99%